Traditional philosophy of the Kazakh music of ХІХ Century - K. D., Seisenbekov; T., Mukyshev; G., Begalinova; M. S, Myltykbayeva (Opción, 2019)
The article aims to investigate the traditional philosophy of the Kazakh music of ХІХ century via deep and comprehensive study of the aesthetics and techniques of artistic expression. The research proves for the first time that the origins of the reform are connected with composing the (specifically written) type of poets’ labor and their breakaway from aesthetics of the oral type of art when the creator is an author and performer of the work in one person. In conclusion, art should not be interesting, but substantial, since the main task of Music, in Abayu, for teaching and edification.